MORPHOLOGICAL CHANGES OF RATS AFTER PERIPHERAL NERVE INJURY AND PHARMACOLOGICAL CORRECTION IN THE EARLY STAGES OF RESEARCH - Demidchuk, A.S. (World of Medicine and Biology, 2015)
More than 60% of injuries of peripheral nerves leading to the clinical picture complete violation of their conductivity, but the surgery did not find macroscopically visible gaps nerves. In recent years, of which authors use neyropeptydnyh effect of pharmacological agents in experiment and clinic for the treatment of facial nerve neuropathy, retinal degeneration, traumatic brain injury, Alzheimer's disease, ischemic stroke The purpose of this research was to study ultrastructure changes of rats’ peripheral nerve in the conditions of its damage and neuropeptides application and without pharmacological correction in 3 weeks after trauma. Research was conducted on white rats which were devided into three groups. In animals of the I, II and III groups the experimental model of sciatic nerve trauma was done. In postoperative period the rats of the first group had any pharmacological correction. The second group rats received сerebrolysinum in the dose of 0,02 mg/kg daily during 21 day postoperatively, the third the group animals received сerebralum in the dose of 0,02 mg/kg daily during three days postoperatively. Morfology study of the rat’s sciatic nerve peripheral stump in 6 weeks after trauma in all three groups of animals was done by electron microscopic methods. For the purpose of microscopy light optical histological material was fixed in 10% solution of neutral formalin, washed and treated samples in cryostat sections, which later imprehnetion solution of silver nitrate impregnation method for rapid elements peryferichnoyi nervous system (Kolomyitsev AK et al., 1981 ).The greatest effect of treatment of damaged nerve occurs when using сerebralum , insofar as regenerate nerve fibers of two types in large quantities, and are unable to recover die apoptosis.
Keywords: peripheral nerve; regeneration; сerebrolysinum; сerebralum